(untitled) (Archive of Conferences, 2021)
The innovative development of the Republic of Uzbekistan is in many ways directly related to the development of priority industries, including the chemical, biochemical, gas and petrochemical industries. Decree of the President of the Republic of Uzbekistan No. PP-4992 dated February 13, 2021 "On measures for further reforming and financial recovery of chemical industry enterprises, development of production of chemical products with high added value" in order to strategically redraw the development of the chemical industry in the new conditions of economic reforms in Uzbekistan.